Absolute recidivism rates predicted by Static-99R and Static-2002R sex offender risk assessment tools vary across samples: a meta-analysis - Helmus, Leslie (Criminal justice and behavior, 2012)
There has been considerable research on relative predictive accuracy (i.e., discrimination) in offender risk assessment (e.g., Are high-risk offenders more likely to reoffend than low-risk offenders?), but virtually no research on the accuracy or stability of absolute recidivism estimates (i.e., calibration). The current study aimed to fill this gap by examining absolute and relative risk estimates for certain Static sex offender assessment tools. Logistic regression coefficients for Static-99R and Static-2002R were combined through meta-analysis (8,106 sex offenders; 23 samples). The sexual recidivism rates for typical sex offenders are lower than the public generally believes. Static-99R and Static-2002R both demonstrated remarkably consistent relative predictive accuracy across studies. For both scales, however, the predicted recidivism rates within each risk score demonstrated large and significant variability across studies. The authors discuss how the variability in recidivism rates complicates the estimation of recidivism probability in applied assessments.